Bank competition, asset allocations and risk of failure: An empirical investigation - John Boyd; Gianni De Nicolò; Abu M. Jalal (Center for Economic Studies and ifo Institute (CESifo), 2010)
This study is an empirical investigation of theoretical predictions concerning the impact of bank competition on bank risk and asset allocations. Recent work (Boyd, De Nicolò and Jalal, 2009, BDNJ henceforth) predicts that as competition in banking increases, the loan-to-asset ratio will rise (under reasonable assumptions), but the probability of bank failure can either increase or decrease. However, the probability of bank failure will fall if and only if borrowers' response to take on less risk as loan rates decline is sufficiently strong. We test these predictions using two samples with radically different attributes. With both, we find that banks' probability of failure is negatively and significantly related to measures of competition. We also find that as competition intensifies, borrower risk decreases and the loan-to-asset ratio increases. These results are consistent with the predictions of the BDNJ model.
Keywords: 330; Bank; Internationaler Wettbewerb; Bankrisiko; Bilanzstrukturmanagement; Bankinsolvenz; Schätzung; Welt; USA